2020
DOI: 10.1017/s0022029920000655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation time and acid casein concentration as nitrogen source on microbial rennet production

Abstract: We evaluated the effects of fermentation time and acid casein content on the microbial rennet obtained by solid-state fermentation using wheat bran as the carbon source. The experiments used two fermentation times (72 and 96 h), while acid casein content was 1.5, 2.0, 2.5, and 3.0 g. Rennet strength from eight enzymatic extracts was measured using pasteurized whole milk. Rennet strength of samples from 72 h of fermentation showed an increase when acid casein content increased. The rennet strength increased at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
2
1
1
Order By: Relevance
“…The effect of casein concentration was not significant against both of spMCA and MCA/PA, probably because of the previous setup near the optimal values. The optimal ratio of casein addition was predicted to be 1.33% w/w, similar to the 1.5% w/w reported by Khademi et al [ 29 ], but in contrast to the 250% w/w reported by Fileto-Pérez et al [ 25 ]. Lower enzyme activity was obtained at lower and higher ratios.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The effect of casein concentration was not significant against both of spMCA and MCA/PA, probably because of the previous setup near the optimal values. The optimal ratio of casein addition was predicted to be 1.33% w/w, similar to the 1.5% w/w reported by Khademi et al [ 29 ], but in contrast to the 250% w/w reported by Fileto-Pérez et al [ 25 ]. Lower enzyme activity was obtained at lower and higher ratios.…”
Section: Discussionsupporting
confidence: 81%
“…Escobar and Barnett [ 22 ] have reported that Rhizomucor miehei cultures reached the stationary phase through 90−120 h. Enzyme yield and activity were decreased after 96 h of incubation, probably due to nutrient depletion, accumulation of organic acids, and lower pH. Similar findings were reported [ 25 , 26 , 47 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Milk-clotting enzymes (MCEs), derived from animals, plants, fungi, and bacteria, are widely applied in cheese manufacturing . However, the low supply of calf rennet worldwide cannot fulfill the rapidly increasing demand for cheese.…”
Section: Introductionmentioning
confidence: 99%